Utilizing the Multiple Mirror Technique to Assess the Quality of Cambodian Trade Statistics - Shintaro Hamanaka (Asian Development Bank (ADB), 2011)
This paper assesses the quality of Cambodia's export and import statistics by comparing them with the statistics of its trade partners. The paper identifies inaccuracies in trade statistics caused by two types of misclassifications: commodity misclassification and direction misclassification. We will thoroughly examine products that are misclassified as different (but similar) products as well as goods to or from a particular country that are misclassified as goods to or from another country. A single bilateral mirror comparison, which is common in the existing literature, does not tell us much about the manner in which misclassifications are committed. Even if we observe a large discrepancy in certain traded commodities between two sides, we cannot immediately conclude which side has generated the inaccurate statistic. In order to overcome this problem, the paper will use the multiple mirror comparison technique. By comparing the results of various bilateral mirror analyses of trade statistics, we can identify which direction and commodity misclassifications have been committed by Cambodia.
hdl:11540/2003
Keywords: C46; F13; 330; quality of trade statistics; misclassification; smuggling; multiple mirror technique; c.i.f./f.o.b. ratio